Theoretical study on activation mechanism of fluorine substitution reactions of Keggin-MAl12 in aqueous solutions. Issue 19 (1st October 2016) - Jin, Xiao-Yan; Liao, Rong-Bao; Huang, Zheng-Jie; Wu, Hai; Zou, Ying; Zhang, Hong
Abstract: The fluorine substitution reactions of Keggin polymeric aluminum species K-MAl12 (M = Al, Ga, Ge) were investigated using density functional theory. Two substitution pathways (associative and dissociative) were simulated. The results show that the replacement of charged tetrahedral center metals causes the change in energy barrier either for associative mechanism or dissociative mechanism. The preferred activation mechanisms are proposed by comparing associative and dissociative barriers for fluorine substitution reactions of three Keggin Al species. The fluorine substitution reactions of Al13 and GaAl12 are inclined to dissociative mechanism and GeAl12 follows an associative mode, indicating a mechanistic variation induced by the alteration of tetrahedral metals. Abstract :